How does domestic and foreign money growth affect the U.S. economy? - Matti Virén (Bank of Finland, 1989)
This paper tests the hypothesis advanced particularly by McKinnon that the U.S. economy is strongly affected by the world supply of money and the U.S. effective exchange rate while the domestic money supply is of minor importance. This currency substitution hypothesis is tested by using monthly data for the floating exchange rate period 1973 - 1988. The empirical results give cle"ar support" to McKinnon's hypothesis.
URN:NBN:fi:bof-201807301768
Keywords: 330